2008
DOI: 10.1080/10538710801916564
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the NICHD Protocol to Enhance the Quantity of Details Obtained from Children with Low Verbal Abilities in Investigative Interviews: A Pilot Study

Abstract: This study explored the impact of the NICHD protocol to enhance the quantity and content of details reported by children with low verbal abilities. Thirty-four children aged from 6 to 14 were interviewed following their experience of sexual abuse. Half the interviews were conducted using the NICHD protocol. Results indicate that NICHD interviews contained more open-ended prompts and more details overall. Open-ended invitations yielded significantly more detailed responses than did close-ended questions for bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
0
22
1
1
Order By: Relevance
“…Indeed, some researchers (Graffam Walker, 1999;Poole & Lamb, 1998) have indicated that older children often see the interview as a test that they must pass successfully. Moreover, recent research has shown that sexually abused children often present below-average cognitive functioning (Daignault & Hébert, 2009;Dion & Cyr, 2008;Dion, Cyr, Richard, & McDuff, 2006), which affects their comprehension of the task at hand and of the questions asked, as well as their capacity to recount their sexual abuse experience. These results suggest that feedback could help investigators improve their use of the protocol when interviewing preadolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some researchers (Graffam Walker, 1999;Poole & Lamb, 1998) have indicated that older children often see the interview as a test that they must pass successfully. Moreover, recent research has shown that sexually abused children often present below-average cognitive functioning (Daignault & Hébert, 2009;Dion & Cyr, 2008;Dion, Cyr, Richard, & McDuff, 2006), which affects their comprehension of the task at hand and of the questions asked, as well as their capacity to recount their sexual abuse experience. These results suggest that feedback could help investigators improve their use of the protocol when interviewing preadolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Successful training programs ensure that interviewers are continually monitored and given specific feedback on their behaviors (Anderson et al, ; Benson & Powell, ; Lamb, Orbach, Hershkowitz, Esplin, & Horowitz, ; Lamb et al, ; Lewy et al, ; Orbach & Lamb, ; Price & Roberts, ; Rischke, Roberts, & Price, ). The feedback interviewers receive can be in‐person or on‐line (Benson & Powell, ; Powell, Guadagno, & Benson, ), as well as written (Dion & Cyr, ; Cyr & Lamb, ; Yi, Jo, & Lamb, ) or involve a combination of these mechanisms (Lamb et al, ; Rischke et al, ; Price & Roberts, ). Training programs often involve trainees conducting practice interviews (Yi, Lamb, & Jo, ; Yi et al, ) and attending group training sessions, which may include peer review (Myklebust & Bjørklund, ; Stolzenberg & Lyon, ; Rischke et al, ).…”
Section: Child Forensic Interviewer Training Studiesmentioning
confidence: 99%
“…In Henry and Gudjonsson (1999, p. 491) emphasized that ‘there is little research on child witnesses with mental retardation’. They reviewed the pioneering study by Dent (1986) and our study of the usefulness of the cognitive interview for children with mild learning disabilities (Milne & Bull, 1996). In their own study children with average or low intelligence (mean IQ=60) witnessed a staged event and the next day were interviewed about it in line with the government's memorandum of good practice .…”
Section: Particularly Vulnerable Witnessesmentioning
confidence: 99%